Evaluating the efficacy of vatiquinone in preclinical models of Leigh syndrome and GPX4 deficiency - Ernst-Bernhard Kayser; Michael Mulholland; Elizaveta A. Olkhova; Yihan Chen; Holly Coulson; Owen Cairns; Vivian Truong; Katerina James; Brittany M. Johnson; Allison Hanaford; Simon C. Johnson (Orphanet Journal of Rare Diseases)
Abstract Background Genetic mitochondrial diseases are a major challenge in modern medicine. These impact ~ 1:4,000 individuals and there are currently no effective therapies. Leigh syndrome is the most common pediatric presentation of mitochondrial disease. In humans, patients are often treated with antioxidants, vitamins, and strategies targeting energetics. The vitamin-E related compound vatiquinone (EPI-743, α-tocotrienol quinone) has been the subject of at least 19 clinical trials in the US since 2012, but the effects of vatiquinone on an animal model of mitochondrial disease have not yet been reported. Here, assessed the impact of vatiquinone in cellular assays and animal models of mitochondrial disease. Methods The efficacy of vatiquinone in vitro was assessed using human fibroblasts and HEK293 cells treated with the ferroptosis inducers RSL3 and BSO + Fe(III)Citrate, the mitochondrial oxidative stress inducer paraquat, and the electron transport chain complex I inhibitor rotenone. The therapeutic potential of vatiquinone in vivo was assessed using the tamoxifen-induced mouse model for GPX4 deficiency and the Ndufs4 knockout mouse model of Leigh syndrome. Results Vatiquinone robustly prevented death in cultured cells induced by RSL3 or BSO/iron, but had no effect on paraquat induced cell death. Vatiquinone had no impact on disease onset, progression, or survival in either the tamoxifen-inducible GPX4 deficient model or the Ndufs4(-/-) mouse model, though the drug may have reduced seizure risk. Conclusions Vatiquinone prevents ferroptosis, but fails to attenuate cell death induced by paraquat or rotenone and provided no significant benefit to survival in two mouse models of disease. Vatiquinone may prevent seizures in the Ndufs4(-/-) model. Our findings are consistent with recent press statements regarding clinical trial results and have implications for drug trial design and reporting in patients with rare diseases.